Freshwater cultured pearls from Kentucky Lake - Data files (S1, S2, S3) - Gabriela Farfan; Chunhui Zhou; Ian Orland; John W Valley (PANGAEA, 2021)
This dataset contains supplementary tables S1, S2, S3 for our publication (Farfan et al, 2021), given as Excel files.
In: Farfan, G et al. (2021): Mineralogical and isotopic data of freshwater cultured pearls from Kentucky Lake with associated lake environmental data [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938370